Hubungan Indeks Massa Tubuh (IMT) Berlebih Dengan Keluhan Nyeri Lutut Pada Karyawan Universitas Islam Bandung Tahun 2021 - Octka Damayanti Pratama; Mudjtahid Ahmad Djojosugito; Yuli Susanti (UNISBA Press, 2022)
Abstract. A lifestyle consists of food intake and daily activity patterns that affect energy metabolism in the body. Sedentary lifestyles and consumption of high-calorie foods can increase the incidence of excess Body Mass Index (BMI). The knee region has an important role in supporting the body. When there is a deviation from the knee axis, there can be an increase in the stress load on the knee region. Excess BMI and heavy physical activity every day can trigger knee pain conditions. The design of this research is analytic observational with a cross sectional study method with a sample of 60 respondents. The body mass index variable was measured using a calibrated anthropometric measuring instrument. The variable level of physical activity was measured using the International Physical Activity Questionnaires-short form (IPAQ-sf) questionnaire, and the variable level of knee pain was measured using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire. In the study, most respondents were aged 31–40 years (46.7%). Most of the respondents were overweight (63.3%) with moderate activity patterns (63.3%) and experienced mild knee pain in daily activities (95%). Although most of the respondents were overweight, and there were complaints of mild knee pain, statistically there was no relationship between excessive BMI and complaints of knee pain (p = 0.317, p > 0.05), while for moderate physical activity with complaints of knee pain, there was no significant relationship. (p = 0.073, p > 0.05). The conclusion of this study is that there is no significant relationship between excess Body Mass Index (BMI) and knee pain complaints in employees of the Islamic University of Bandung. Abstrak. Gaya hidup terdiri dari asupan makanan dan pola aktivitas sehari-hari mempengaruhi metabolisme energi dalam tubuh. Sedentary lifestyle dan konsumsi makan tinggi kalori dapat meningkatkan kejadian Indeks Massa Tubuh (IMT) berlebih. Regio lutut memiliki peran penting dalam menopang tubuh, ketika terjadi deviasi dari axis lutut dapat terjadi peningkatan beban stress pada regio lutut. IMT berlebih dan aktivitas fisik berat setiap harinya dapat menginisiasi kondisi nyeri lutut. Desain penelitian ini analitik observasional dengan metode cross sectional study dengan sampel sebanyak 60 responden. Variabel indeks massa tubuh diukur menggunakan alat ukur antropometri terkalibrasi. Variabel tingkat aktivitas fisik diukur menggunakan kuesioner International Physical Activity Questionnaires-short form (IPAQ-sf) dan variabel tingkat nyeri lutut di ukur menggunakan kuesioner Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Pada penelitian didapatkan responden paling banyak berusia 31-40 tahun (46,7%), sebagian besar responden mengalami overweight (63,3%) dengan pola aktivitas kategori sedang (63,3%) dan mengalami nyeri lutut ringan dalam berkegiatan sehari-hari (95%). Walaupun sebagian besar responden mengalami overweight dan untuk keluhan nyeri lutut ringan namun secara statistic tidak ada hubungan antara IMT berlebih dengan keuhan nyeri lutut (p= 0,317, p>0,05) sedangkan untuk aktivitas fisik sedang dengan keluhan nyeri lutut tidak terdapat hubungan yang signifikan (p=0,073, p>0,05). Simpulan dari penelitian ini adalah tidak terdapat hubungan yang signifikan antara Indeks Massa Tubuh (IMT) berlebih terhadap keluhan nyeri lutut pada karyawan Universitas Islam Bandung.